ANALISA PENGARUH SUHU DAN WAKTU PEMANASAN PADA NYLON FILM TERHADAP MAMPU BENTUK ZIPPER - Mohamad Faizal; Fahmi Wahyudi (Bina Teknika, 2017)
Ultrasonic Welding has been used to join the thermoplastic material of about 35 years. Now, Ultrasonic Welding has been widely used not only for the thermoplastic material, but also can be used for all kinds of industries, one of which is the textile industry. Ultrasonic Welding has many advantages economically and efficiency. In its use of the zipper industry, Ultrasonic Welding used to join between components to the surface of the film nylon zipper. However, the wrong calculation of the temperature and the length of time could caused the strength of nylon films was reduced to cause permanent damage. This study aims to determine the temperature and duration of heating time. Ultrasonic Welding is used Branson type with power supply 40 kHz / 60 W with a maximum current of 3A. Booster type used is standard series M8 x 1:25 Horn 40 kHz with titanium material. Converter used CH30 with a maximum continuous use at 60 W. attachment method used is butt joint with a gap between the horn surface is ¼ inch zipper.Thermoplastic material in this case used nylon 66.